PERBEDAAN KONSENTRASI KARAGENAN TERHADAP SIFAT FISIKOKIMIA DAN ORGANOLEPTIK JELLY DRINK ROSELA-SIRSAK - Gani, Yohana Fransisca; Suseno, Thomas Indarto Putut; Surjoseputro, Sutarjo (Jurnal Teknologi Pangan dan Gizi, 2014)
The experimental design is Randomized Block Design with one factor which is carrageenan concentration and seven factor levels which are 0.20%; 0.25%; 0.30%; 0.35%; 0.40%; 0.45%; and 0.50% (m/v) with four replications. The parameters tested are physicochemical test (flow rate, viscosity, pH, and syneresis days 1, 7, and 14 storage) and organoleptic test (color, suction power, and taste). The data is statically analyzed using ANOVA (Analysis of Variance) test at α = 5% and continued by DMRT (Duncan’s Multiple Range Test) at α = 5%. The increase of carrageenan concentration is expected significantly affect the physicochemical and organoleptic properties of rosella-soursop jelly drink. The results from this research showed that increasing the concentration of carrageenan significantly affect the value of flow rate, viscosity, pH, and syneresis days 1, 7, and 14 storage of rosella-soursop jelly drink. The higher the concentration of carrageenan increases the value of viscosity, pH, syneresis days 1, 7, and 14 storage but decreases the value of flow rate. Increasing the concentration of carrageenan significantly affect the value of preferences for color, suction power, and taste of rosella-soursop jelly drink. The best treatment of rosella-soursop jelly drink is addition 0.30% carrageenan concentration and fiber content for rosella-soursop jelly drink with addition of 0.40% carrageenan concentration is 0.66% (wb).